Oscillatory dynamics track motor performance improvement in human cortex. - Stefan Dürschmid; Fanny Quandt; Ulrike M Krämer; Hermann Hinrichs; Hans-Jochen Heinze; Reinhard Schulz; Heinz Pannek; Edward F Chang; Robert T Knight (PLoS ONE, 2014)
Improving performance in motor skill acquisition is proposed to be supported by tuning of neural networks. To address this issue we investigated changes of phase-amplitude cross-frequency coupling (paCFC) in neuronal networks during motor performance improvement. We recorded intracranially from subdural electrodes (electrocorticogram; ECoG) from 6 patients who learned 3 distinct motor tasks requiring coordination of finger movements with an external cue (serial response task, auditory motor coordination task, go/no-go). Performance improved in all subjects and all tasks during the first block and plateaued in subsequent blocks. Performance improvement was paralled by increasing neural changes in the trial-to-trial paCFC between theta ([Formula: see text]; 4-8 Hz) phase and high gamma (HG; 80-180 Hz) amplitude. Electrodes showing this covariation pattern (Pearson's r ranging up to .45) were located contralateral to the limb performing the task and were observed predominantly in motor brain regions. We observed stable paCFC when task performance asymptoted. Our results indicate that motor performance improvement is accompanied by adjustments in the dynamics and topology of neuronal network interactions in the [Formula: see text] and HG range. The location of the involved electrodes suggests that oscillatory dynamics in motor cortices support performance improvement with practice.